The Impact of Teacher Social Competence for the Result of Social Subject Grade VIII in SMP Negeri 7 Pematang Siantar - Andre Syahputra Sitohang; Sotarduga Sihombing; Anton Luvi Siahaan (MultiTech Publisher, 2023)
This research aims to determine the influence of teacher social competence on student learning outcomes in social studies subjects in class VIII SMP Negeri 7 Pematang Siantar. The variables in this research are teacher social competence as the independent variable and learning outcomes as the dependent variable. This type of research is quantitative research with a quantitative descriptive data analysis approach, with a research population of all class VIII students at SMP Negeri 7 Pematang Siantar and a research sample of class VIII students at SMP Negeri 7 Pematang Siantar consisting of 146 students selected using simple random sampling ( formula Slovin ). Data collection techniques use questionnaires and documentation. The results of this research show that: there is a positive and significant influence of teacher social competence on learning outcomes. This result can be seen in the t test where the t value is calculated Teacher social competence ( 2.551 ) > t table value (1.65550) which means this variable is significant. The R Square coefficient of determination test was found to be 0.043, which means that 4.30% of the teacher's social competence variable influences student learning outcomes at SMP Negeri 7 Pematang Siantar and the remaining 95.70% is the influence of other variables not examined in this research.